The psychology of advertising - Fennis, Bob Michaël, 1968- (Routledge, Taylor & Francis Group, 2021)
"The Psychology of Advertising offers a comprehensive exploration of theory and research in (consumer) psychology on how advertising impacts the thoughts, emotions, and actions of consumers. It links psychological theories and empirical research findings to real-life industry examples, showing how scientific research can inform marketing practice. Advertising is a ubiquitous and powerful force, seducing us into buying wanted and sometimes unwanted products and services, donating to charitable causes, voting for political candidates, and changing our health-related lifestyles for better or worse. This revised and fully updated third edition of the Psychology of Advertising offers a comprehensive and state-of-the art overview of psychological theorizing and research on the impact of online and offline advertising and discusses how the traces consumers leave on the internet (their digital footprint) guides marketers in micro-targeting their advertisements. The new edition also includes new coverage of big data, privacy, personalization, and materialism, and engages with the issue of the replication crisis in psychology, and what that means in relation to studies in the book. Including a glossary of key concepts, updated examples, and illustrations, this is a unique and invaluable resource for advanced undergraduate and graduate students and instructors. Suitable for psychology, advertising, marketing, and media courses. it is also a valuable guide for professionals working in advertising, public health, public services and political communication"--